Advancing Carbon Neutrality: From Green-Oriented to Climate-Driven Public Finance - Liu, Wenjie; Okitasari, Mahesti (WIMAYA, 2023)
This article presented how the existing landscape of green public finance in China works in practice with a focus on government spending, taxation, and government fund, and assessed the alignment of these financial avenues with the goals of achieving carbon neutrality. The findings suggest that while China does not have a specific plan for public climate finance, the climate goals have been systematically integrated into key public finance avenues. However, the relevance and alignment of each component to the climate goals vary. The findings yield several insights for future policymaking in financing China's net-zero goal. It is recommended that China not only establish a green or climate budget system that incorporates climate considerations into decision-making processes but also proactively explores the potential of leveraging government expenditure and fiscal revenue to expand climate financing. On the expenditure side, China can increase its fiscal spending with a specific focus on green-oriented and climate-oriented initiatives, both in terms of overall size and proportion to GDP. On the revenue side, it is necessary to assess the feasibility of aligning tax measures with climate goals and explore potential synergies with other financial mechanisms. Ultimately, this article addressed the importance of accelerating the low-carbon transition with support from a green-oriented to a climate-driven approach in public finance.